2019
DOI: 10.20546/ijcmas.2019.801.149
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Knowledge, Attitude and Practices among Postgraduates and CRRIs in a Tertiary Care Hospital, Chennai, India

Abstract: The importance of hands in the transmission of hospital infections has been well demonstrated and hand hygiene reduces the prevalence of hospital acquired infections. The study was designed to evaluate the knowledge, attitude, practices and satisfaction of the available facilities among Postgraduates and CRRIs and to identify the gaps in hand hygiene practices and to implement an Institutional program on hand hygiene policy. A self-administered questionnaire was used. The study was conducted between September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is conceivable that contaminated hands are responsible for spreading the infection, which can lead to the death of patients. Sufficient knowledge about hand hygiene increases positive attitudes 12,20,21 .compliance of healthcare workers to hand hygiene guidelines are reportedly poor. It is important therefore to instill adequate knowledge and good attitudes and practices at the time of primary training of the healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that contaminated hands are responsible for spreading the infection, which can lead to the death of patients. Sufficient knowledge about hand hygiene increases positive attitudes 12,20,21 .compliance of healthcare workers to hand hygiene guidelines are reportedly poor. It is important therefore to instill adequate knowledge and good attitudes and practices at the time of primary training of the healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…WHO, in 2009, adopted new global guidelines for hand hygiene 4 . The duration of the entire procedure is 40-60 seconds for hand hygiene with water and soap, [20][21][22][23][24][25][26][27][28][29][30] seconds for hand hygiene with alcoholbased hand rub. In the guidelines, WHO also appointed five critical moments for hand hygiene, which are: before touching a patient (Moment 1), before a procedure (Moment 2), after a procedure (Moment 3), after touching a patient (Moment 4) and after touching a patient's surroundings (Moment 5).…”
Section: Introductionmentioning
confidence: 99%
“…Ravichandran et al ( 2019 ) study in a medical college in India, and Appiah-Brempong et al ( 2020 ) study among primary school children in Ghana showed that knowledge of hand hygiene may not necessarily translate into handwashing behaviour nor positive intentions or attitudes toward handwashing. Even though the knowledge of hand hygiene is known to influence proper handwashing behaviour, the fear of disease infection (perceived susceptibility) and its severity (perceived severity) largely determines the compliance to hygiene practices, even in the midst of barriers (Gillespie, 2013 ).…”
Section: Introductionmentioning
confidence: 99%